Join the conversation on IDNLearn.com and get the answers you seek from experts. Discover trustworthy solutions to your questions quickly and accurately with help from our dedicated community of experts.

Write a recursive sequence that represents the sequence defined by the following explicit formula:

[tex]\[ a_n = -7 + 10(n - 1) \][/tex]

Answer:

[tex]\[ a_1 = \square \][/tex]

[tex]\[ a_n = a_{n-1} + \square \][/tex]


Sagot :

Certainly! Let's write the recursive sequence that corresponds to the given explicit formula:
[tex]\[ a_n = -7 + 10(n-1) \][/tex]

### Step-by-Step Solution:

1. Identify the first term:
The explicit formula is provided, which helps us find the first term when [tex]\( n = 1 \)[/tex]:
[tex]\[ a_1 = -7 + 10 \times (1 - 1) \][/tex]

2. Simplify the expression for [tex]\( a_1 \)[/tex]:
[tex]\[ a_1 = -7 + 10 \times 0 \][/tex]
[tex]\[ a_1 = -7 \][/tex]

So, the first term of the sequence is:
[tex]\[ a_1 = -7 \][/tex]

3. Determine the recursive relationship:
From the explicit formula, we can see that each term increases by a fixed amount (10) compared to the previous term. To represent this in a recursive formula, we express [tex]\( a_n \)[/tex] in terms of [tex]\( a_{n-1} \)[/tex]:

Since we know:
[tex]\[ a_n = -7 + 10(n-1) \][/tex]
and for [tex]\( n-1 \)[/tex]:
[tex]\[ a_{n-1} = -7 + 10((n-1)-1) = -7 + 10(n-2) \][/tex]

Subtracting these two sequences:
[tex]\[ a_n - a_{n-1} = [-7 + 10(n-1)] - [-7 + 10(n-2)] \][/tex]
[tex]\[ a_n - a_{n-1} = 10(n-1) - 10(n-2) \][/tex]
[tex]\[ a_n - a_{n-1} = 10 \][/tex]

Therefore, each term [tex]\( a_n \)[/tex] is 10 more than the previous term [tex]\( a_{n-1} \)[/tex].

Now, we write the recursive formula:
[tex]\[ a_n = a_{n-1} + 10 \][/tex]

### Final Recursive Sequence:

Given the sequence's first term and the recursive relationship, the recursive sequence can be written as:
[tex]\[ a_1 = -7 \][/tex]
[tex]\[ a_n = a_{n-1} + 10 \text{ for } n > 1 \][/tex]

Thus, we have successfully converted the explicit formula into a recursive sequence.